Teaching reading to youth with fragile X syndrome: Should phonemic awareness and phonics instruction be used? - Randel, Allison (EBP Briefs, 2015)
CLINICAL QUESTION: Would a child with fragile X syndrome benefit more from phonemic awareness and phonics instruction or whole-word training to increase reading skills? METHOD: Systematic review STUDY SOURCES: PsycINFO SEARCH TERMS: Fragile X or Down Syndrome or Cognitive Impairment or Cognitive Deficit or Cognitive Disability or Intellectual Disorder or Intellectual Delay or Intellectual Disability or Mental Retardation AND Whole Word or Sight Word or Phonological Awareness or Phonics NUMBER OF STUDIES INCLUDED: FXS = 0; DS = 6; ID = 17 PRIMARY RESULTS: 1. There are currently no published peer-reviewed treatment studies testing reading interventions for children with fragile X syndrome. 2. Phonological awareness and reading outcomes are correlated in children with fragile X syndrome, similar to the pattern seen in typical development. 3. There is converging empirical evidence that phonologically-based approaches, often included as part of a comprehensive program, can be beneficial with children and adolescents with other developmental disabilities, including Down syndrome, intellectual disabilities, and autism spectrum disorder. CONCLUSIONS: There is a need for more research to determine what types of reading interventions are beneficial when working with children with fragile X syndrome. Given the lack of published empirical research in this area, clinicians should rely on existing evidence-based treatment data and professional judgment when determining which course of treatment to implement.